Development of foot care instrument and internal consistency test in the rural area - Parliani; Tri Wahyuni (UM Purwokerto Press, 2020)
Currently, there are some comprehensive assessment tools for DFU. There is only one screening tool, but only assess risk of neuropathy, there is no complete of foot care assessment. The develop of foot care instrument is important for the nurses to provide health services and seek to eliminate physical, emotional, mental, and socio-cultural patient needs and also they play an important role in the care of diabetes .This descriptive study aimed: 1) to develop the instrument of foot care for diabetic patient, and 2) to test internal consistency in the rural area. The tool development were using: 1) literctivature review, 2) defining and categorize the item and 3) Testing the internal consistency using 23 respondents in Desa Kerawang and Desa Sumber Agung,Kubu Raya.Cronbachs Aplha were to analyze the internal consistency.The results showed that the instrument was developed as followed internal consistency used Cronbach’s Alpha was 0.893 for the item which can be used and 0.991 for the item which can be done in the rural area.The total items of this study consisted of: 1) Foot care education, consisting of a) knowledge of foot care, b) foot care behavior, c) amputation risk, d) mortality risk, d) interpretation of monofilament examination, 2) foot care diabetes, a) foot and foot examination, b) routine foot hygiene, c) walking barefoot, d) using proper footwear, e) cutting toe nails, f) avoiding the use of anything rough on the feet, g) professional care when open wounds and lesions in the leg, i) routine foot examination by professionals, 3) routine foot examination, a) peripheral neuopathy, b) history of ulcer or amputation, c) foot deformity, d) peripheral arterial disease, e) level of glycated hemoglobin, 4) Diabetic foot exercises, 5) Self-care management, 6) Supporting factors consist of a) footwear, b) digital silicon divices, c) antifungal treatment, d) elastic compression stocking.In conclusion the instrument of foot care has developed and reliable in rural area. Nurses and people who work with diabetic patients can use the instrument take care of patients’ foot. Further study should examine other test of validity and reliability.